Evaluación de variedades de arroz 94A: ciclo 94-95 - Marcia Suárez, Larry José. (Granada (Nicaragua), 1995)
Sumario (Es)
Cuadros; 2 ref.
Keywords: ORYZA SATIVA; ENSAYOS DE VARIEDADES; NICARAGUA; CITOGENETICA Y MEJORAMIENTO